Interferon consensus sequence-binding protein, a member of the interferon regulatory factor family, suppresses interferon-induced gene transcription. - Nelson, N (1993)
We previously isolated a cDNA clone encoding interferon consensus sequence-binding protein (ICSBP), a member of the interferon regulatory factor (IRF) family, that binds to the interferon (IFN)-stimulated response element (ISRE) of many IFN-regulated genes. In this investigation, we studied the functional role of ICSBP by transient cotransfection of ICSBP cDNA with IFN-responsive reporter genes into the human embryonal carcinoma cell line N-Tera2. These cells were shown not to express ICSBP or IRF-2, thus allowing functional analysis of transfected cDNAs. Cotransfection of ICSBP into cells treated with retinoic acid or any of the IFNs (alpha, beta, or gamma) repressed expression of a chloramphenicol acetyltransferase reporter driven by the major histocompatibility complex class I gene promoter. Similarly, ICSBP repressed expression of chloramphenicol acetyltransferase reporters driven by the ISREs of the 2'-5' oligoadenylate synthetase, guanylate-binding protein, and ISG-15 genes in IFN-treated cells. The repression was dependent on the presence of the ISRE in the reporter. Deletion analysis showed that the putative N-terminal DNA binding domain of ICSBP by itself is capable of mediating the repression. Using the same cotransfection conditions as for ICSBP, a similar repression of these reporters was observed with IRF-2. Finally, ICSBP repressed the IRF-1-mediated induction of major histocompatibility complex class I and IFN-beta reporters in the absence of IFN or retinoic acid. Taken together, these results suggest that ICSBP is a negative regulatory factor capable of repressing transcription of target genes induced by IFN, retinoic acid, or IRF-1.